2012
DOI: 10.1590/s1982-56762012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Resistência física de bainhas de plantas de arroz supridas com silício e infectadas por Rhizoctonia solani

Abstract: RESUMOEste trabalho objetivou associar a deposição de silício (Si) nas bainhas de plantas de arroz ao aumento da resistência física à infecção por Rhizoctonia solani. Plantas das cultivares suscetíveis BR-Irga 409 e Labelle foram cultivadas em solução nutritiva contendo (+Si) ou não (-Si) Si. A concentração de Si nas bainhas das plantas supridas com Si e inoculadas com R. solani aumentou significativamente em relação às plantas não supridas com Si reduzindo o comprimento relativo da lesão às 96 horas após inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
3
Order By: Relevance
“…However, according to Rezende et al (2009) andZanão Junior et al (2009), the management of rice brown spot with Si is effective when it is applied in the soil. The severity of sheath blight, caused by the fungus Rhizoctonia solani in rice plants grown in nutrient solution, was also reduced (Schurt et al, 2012).…”
Section: Silicon In Disease Control In Monocotyledonsmentioning
confidence: 99%
“…However, according to Rezende et al (2009) andZanão Junior et al (2009), the management of rice brown spot with Si is effective when it is applied in the soil. The severity of sheath blight, caused by the fungus Rhizoctonia solani in rice plants grown in nutrient solution, was also reduced (Schurt et al, 2012).…”
Section: Silicon In Disease Control In Monocotyledonsmentioning
confidence: 99%
“…[21] Among the plant products obtained from L. microphylla, essential oils stand out, which are responsible for various physical, chemical, and biological properties of the family as a whole. [22] These volatile oils are abundant in monoterpenes and possess larvicidal activity against Aedes aegypti larvae, [23] antifungal and antibacterial properties, [24,25] and antioxidant activity. [26] Previous studies conducted by our group have shown that the essential oil extracted from the leaves of L. microphylla is mainly composed of the monoterpenes thymol, carvacrol, and p-cymene, and it exhibits an antitumor effect in vitro on the K562 cell lines (human leukemia) and Sarcoma 180 (murine tumor), as well as in vivo activity in a sarcoma 180 model.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Kim et al (2002), essa dupla camada sílica-cutícula atrasou a penetração de Pyricularia grisea nas folhas de arroz (Kim et al, 2002). Schurt et al (2012) observaram que as bainhas obtidas das plantas das cultivares BR-Irga 409 e Labelle com concentração de Si variando de 1,9 a 2,5 dag kg -1 tinham maior força física à penetração de uma agulha, o que explicou a redução no comprimento relativo das lesões da queima das bainhas. O Si pode estar associado ao complexo lignina-carboidrato na parede celular das plantas de arroz (Inanaga et al, 1995), contribuindo para a resistência dessa planta às doenças (Datnoff et al, 2007).…”
Section: Introductionunclassified